Challenges and strategies in implementing the 3k-CBT Module in secondary schools - Abdullah, N.; Mudayat, N.A.; Othman, Mohd Hatta; Yusof, M.D.A; Yasin, N.M.; Nordin, M.H.A (2025)
The implementation of the 3K-CBT Module (Self-Concept, Sense of Belonging, and Engagement) in secondary schools aims to support truant students in strengthening their selfconcept, fostering a sense of belonging, and enhancing their engagement in academic and social activities. Despite its potential in addressing truancy, the module's implementation encounters several significant challenges. These include students’ lack of motivation, limited support from teachers and school administrators, constraints related to time and school schedules, the influence of peers and school environment, inadequate resources and materials, and the transition to digital learning, particularly during the COVID-19 pandemic. This article examines these challenges in detail and explores effective strategies to overcome them, such as motivational approaches, comprehensive school support, flexible scheduling, peer mentoring, resource optimization, and the integration of digital tools. By addressing these barriers, this article provides practical guidance for educators and school counselors to implement the 3K-CBT Module more effectively, ensuring meaningful and sustainable behavioral changes among students at risk of truancy.